Innovative strategic planning for a sustainable green university: University of Ruhuna, Sri Lanka - Amarasena T.S.D; Chandana E.P.S; Ratnasekera D; Hasini K.K.L (Journal of Sustainability Perspectives, 2022)
University of Ruhuna (UOR) consists of ten faculties that spread over 366 acres in six different locations in the Southern Province of Sri Lanka. Economically viable and mutually benefited public-private partnerships, which ensure the common direction for the different goals of stakeholders, are the principles of strategic green planning of the University. This paper presents two key sustainable initiatives of UOR. The proposed strategic landscaping project has been focused to utilize the open space which accounts for 60-70% of the total land area. The total open space will be divided into manageable zones based on geographical characteristics. Private sponsorships will be sought to cover the initial capital and maintenance cost, allowing sponsors to do selectedpromotional activities within their zones. The second project is the establishment of a sustainable, modern agribusiness venture. Thirty acres of land will be rented out for a private company and the company has to share the profit with the University. University will provide consultation and technical support to the project. Cultivation of Cinnamon, Pepper and other unique spicy crops, production of organic fertilizer and bio char, protected agriculture project, Cinnamon oil extraction plant and solar power project are the key components of this initiativeKeyword: Green university, Public-private partnerships, Strategic planning, Sustainable